Cost Management Practices in the Aquaculture Industry - Angelica R. Carolino; Arly N. Visperas; Jhona Jane C. Camba; Kristine Joy S. Castillo; Marylou G. Malapit; Richiel G. Nidoy; Lesel O. SulaSula (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Aquaculture is a big source of income for people living near the coast. For fish farmers, keeping track of costs is really important if they want their farms to keep running and actually make money. This study looked at how fish farmers in Anda, Labrador, and Binmaley, Pangasinan manage their costs, and how these practices relate to their backgrounds and business details. The research supports SDG 8, SDG 12, SDG 14, and SDG 17. The researchers used a quantitative, descriptive approach and surveyed 30 fish farmers with a validated questionnaire based on a 4-point Likert Scale. They used frequency counts and percentages to describe the participants and the average weighted mean to measure cost management practices. Spearman’s Rank-order Correlation identified significant relationships. The results showed that most farmers are careful with their money—they budget, monitor, and control their costs regularly. We also noticed that farmers with more experience and those who make more sales are usually better at managing their money. This means that learning from experienced farmers and sharing good practices could really help those who are just starting out.